PERKEMBANGAN INTERPRETASI “KE BELAKANG TABIR” (IBR. 6:19, 20) DI DALAM GEREJA MASEHI ADVENT HARI KETUJUH - Franklin Hutabarat (Jurnal Koinonia, 2014)
In the study of the heavenly sanctuary and Christ's ministry in it, theinterpretation of the phrase “within the veil” (Heb. 6:19-20) and its implicationshave become one of crucial contentious theological issues among interpreterswithin the Seventh-day Adventist (SDA) Church. In the 160 year history of theSDA Church, there have been crucial theological debates on the interpretation ofthe phrase. Many SDA Church administrators, ministers, and scholars haveagreed and disagreed with one another on the interpretation of the phrase and itsimplications. The debate over the interpretation of the phrase "within the veil"among Adventist scholars has resulted in the proposition of differentinterpretations among Adventist theologians. The main question this studyseeks to answer is, How have the various interpretations of the phrase “withinthe veil” (Heb. 6:19-20) been developed within the SDA Church history? What,then, are the implications of each different interpretation in the study of theheavenly sanctuary and Christ's intercessory ministry in the heavenly sanctuary?